PENGARUH PLATELET-RICH PLASMA (PRP) TERHADAP PROLIFERASI DAN VIABILITAS HUMAN DERMAL FIBROBLAST (HDF) DALAM KONSENTRASI GLUKOSA TINGGI - Hadi, Restu Syamsul; Kusumah, Indra; Sandra, Yurika (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTThe administration of Platelet Rich Plasma (PRP) is expected to be a supplement for treatment of diabetic wounds and hyperglycemia by increasing growth factors. The purpose of this study was to examine the effect of Platelet Rich Plasma (PRP) on the proliferation and viability of human dermal fibroblast (HDF) in high glucose conditions, as a model for healing diabetic wounds in vitro. HDF cells are grown in DMEM medium containing high glucose which are then with PRP. To measure the effect of PRP on the HDF cell proliferation, CCK-8 kit was used and evaluated by using a microplate reader. To evaluate the viability of HDF, an automated cell counter. The results of the research showed that PRP stimulate the HDF cells proliferation. The optimal dose of PRP to increase HDF cell proliferation is at dose of PRP 10%.  Supplementation of PRP is significantly increased cell viability and HDF cell counts within 48 hours. The results showed PDGF growth factor secreted by PRP is increased significantly. The conclusion is PRP stimulated HDF cell proliferation and viability in a high glucose condition. This finding support the used of PRP as a therapy for diabetic wounds.  Keywords: proliferation, viability, human dermal fibroblast, platelet-rich plasma, diabetic